PENDIDIKAN KARAKTER DALAM KONTEKS PENDIDIKAN ISLAM - Mariani Mariani (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
Education is a process of forming human character that leads to independent life, requires a mature and planned arrangement in order to improve human quality. Character education is an important issue that is often discussed by all parties. This issue has strengthened because there has been an erosion of noble values such as honesty, decency, and togetherness which form the identity of the Indonesian nation. The root of the problem is that formal education in schools prioritizes intellectual intelligence, while emotional and spiritual intelligence is neglected from the national character building agenda. To restore the lost noble values, it is necessary to innovate the curriculum with an emphasis on character education. In this case Islamic education can be used as a reference. Because Islamic Education which aims to form a personality with akhlakul karimah which is ontologically based on the values imprinted in the Qur'an and Hadith is in line with the desired character education.